Multi-Timepoint Metabolic Fingerprinting of a Post-Episode Period of Hypoglycemia and Ketoacidosis Among Children With Type 1 Diabetes - Małachowska, Beata; Pietrowska, Karolina; Młynarski, Wojciech; Szadkowska, Agnieszka; Krętowski, Adam; Ciborowski, Michał; Fendler, Wojciech (Frontiers in Molecular Biosciences, 2022)
Background: Acute complications of type 1 diabetes mellitus such as diabetes ketoacidosis (DKA) and hypoglycemia (HG) are detrimental in a short- and long-term perspective. Restoration of normoglycemia and correction of pH do not mean that all metabolic disturbances caused by HG or DKA are immediately reversed. Aim: This study aimed to identify serum metabolic changes caused by an episode of DKA and HG that may indicate the mechanisms contributing to long-term consequences of DKA/HG. Materials and methods: Four groups of children with type 1 diabetes were recruited. The first two study groups included patients after an episode of DKA or HG, respectively. Additionally, two comparative groups were recruited—children with established type 1 diabetes (EDM) and patients with newly diagnosed diabetes without diabetes ketoacidosis (NDM). Serum samples were collected in three group-specific time points (since the hospital admission): HG 0h-12h–48h; DKA or NDM 0h-24h–72 h; and one random fasting sample from patients with EDM. Two batches of 100 samples each were created: for DKA batch 20 × 3 DKA patients, 10 × 3 NDM and 10 EDM; for HG batch: 10 × 3 HG patients, 25 EDM and 15 × 3 NDM. All patients within the batches were age and sex matched. Metabolic fingerprinting was performed with LC-QTOF-MS. Results: Four metabolites were associated with a DKA episode occurring in the preceding 72 h: three were found higher after the DKA episode versus comparative groups: lysophosphatidylcholine (LPC) (18:1), sphingomyelins (SM) (34:0 and d18:0/15:0), and one was found lower: LPC (18:0). Similarly, four metabolites were identified for the HG episode in the last 48 h: three were found higher after the HG episode versus comparative groups: two lysophosphatidylethanolamines (LPE) (18:2 and 20:3) and one LPC (18:2); and one was found lower after the HG episode: oxy-phosphatidylocholine (PC O-34:4). Conclusions: We found eight metabolites whose levels may be traced in the serum, indicating the DKA or HG episode for up to 72 h and 48 h, respectively. Acute complications of diabetes may cause persistent metabolic disturbances long after pH and glucose level normalization.